Insights into EFL Teachers’ and Students’ Perspectives on Communicative Skills Represented in English Textbooks - Tu, Tran Phan Ngoc; Thao, Tran Quoc (VNU Journal of Science: Education Research, 2020)
Course books play an integral part in the process of teaching and learning in general and that of English language teaching and learning. Additionally, it is vital to choose appropriate course books for students to develop their communicative skills. In the context of Vietnam, the new English textbooks for high school students have been designed in an attempt to enhance the communication competence among Vietnamese high school students. Within such a context, this study aims at exploring EFL teachers and students’ perspectives on communicative skills represented in the new English textbooks grade 10. This study involved 42 students in answering a questionnaire and 5 teachers in responding the interview questions. The findings indicated that the new English textbooks grade 10 could improve their communicative skills. Specifically, the activities designed in the textbooks reinforced the communicative skills among students. Furthermore, language provided in the textbooks is appropriate and conducive for students, and the subject and content could aid students’ communicative skills. Such preliminary findings are hoped to contribute to a better understanding of the new English textbooks in English language learning in Vietnamese context.